2020
DOI: 10.1177/1357633x20919308
|View full text |Cite
|
Sign up to set email alerts
|

Tele-orthopaedics: A systematic mapping study

Abstract: Introduction The use of telemedicine in orthopaedics can provide high-quality orthopaedic services to patients in remote areas. Tele-orthopaedics is widely acknowledged for decreasing travel, time and cost, increasing accessibility and quality of care. In the absence of a comprehensive review on tele-orthopaedics applications and services, here, we systematically identify and classify the tele-orthopaedic applications and services and provide an overview of the trends in the field. Methods In this study, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 92 publications
1
30
0
1
Order By: Relevance
“…Previously, several studies outside India have found telemedicine to be an effective method of administering healthcare services for orthopedic patients. 12 , 13 , 14 It reduces the inconvenience of long travel distance, costs, and added discomfort to the patient. In the current COVID-19 pandemic, telemedicine can help in reducing the physical load on already overburdened orthopedic OPDs and reduce the risk of disease transmission to the patient as well as the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies outside India have found telemedicine to be an effective method of administering healthcare services for orthopedic patients. 12 , 13 , 14 It reduces the inconvenience of long travel distance, costs, and added discomfort to the patient. In the current COVID-19 pandemic, telemedicine can help in reducing the physical load on already overburdened orthopedic OPDs and reduce the risk of disease transmission to the patient as well as the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, people might be able to track their vital signs or other biomarkers through the use of digital health programs and wearable sensor technologies that are connected to applications on the device (2). The delivery of orthopedic services at a distance is safe and effective with minimum pitfalls and undesirable events which will ultimately improve the effectiveness of rehabilitation after orthopedic surgery (5)(6)(7). This new type of orthopedic delivery bridges the problem of distance between patients, doctors, and physiotherapists, and eventually minimizes the risk of SARS-CoV-2 transmission by avoiding human contact.…”
mentioning
confidence: 99%
“…Currently, audiovisual-assisted meetings have been incorporated into orthopedic practice given the evidence that they are as effective or at least not inferior to those obtained with conventional face-to-face visits (5). This new form of medical services facilitates the exchange of information between different parties, including specialists, general practitioners, physiotherapists, and patients (6). Virtual consultations and rehabilitation in orthopedic services have been proven to be cost-effective from the perspective of the community and medical providers and reported to increase patient satisfaction, reduce travel and save time for the patients, and minimize costs.…”
mentioning
confidence: 99%
See 2 more Smart Citations